THE MOST EFFECTIVE AND APPROACHABLE METHODS OF ENGLISH LANGUAGE TEACHING - Sakhibova Nigora Turgunovna (European Science Publishing, 2024)
This article is detailed about the effective methods of teaching English to children in primary grades. In this article, you can learn about meaningful and interesting ways to teach English to children. Also, in this article, various methods and ways of teaching English to the younger generation from preschool and elementary grades are considered and studied. Teaching foreign languages to the young generation from their childhood has many advantages. One of the most important factors is that they love the language from childhood and arouse their interest in language learning.
Keywords: elementary, English, children, teaching, fun, song, activities, explanation, quick and easy, young children, mental, physical, teacher, sounds.